PENGARUH KEPEMILIKAN MANAJERIAL, LEVERAGE, PROFITABILITAS, UKURAN, DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN INFORMASI PERTANGGUNGJAWABAN SOSIAL PERUSAHAAN PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI - Nasir, Azwir; Kurnia, Pipin; Hakri, Teguh Dheki (Jurnal Ekonomi, 2013)
The purpose of this research is to give an overview the practice of the socialresponsibility information disclosure conducted food and beverage company listedon the Indonesia Stock Exchange and determine the effect of managerialownership, leverage, profitability, size, and firm age influence corporate socialresponsibility disclosurePopulation in this research is all the food and beverage company listed on theIndonesia Stock Exchange (ICMD 2011). At ICMD is known that the number offood and beverage companies are 18 companies listedThe results of this research are (1) Managerial ownership has no effect significantinfluence of corporate social responsibility information disclosure, (2) Leveragesignificant influence of corporate social responsibility information disclosure, (3)Profitability has no effect significant influence of corporate social responsibilityinformation disclosure, (4) Size has no effect significant influence of corporatesocial responsibility information disclosure, (5) Firm age significant influence ofcorporate social responsibility information disclosure.Keywords :Corporate sosial responsibility disclosure, managerial ownership,leverage, profitability, size, firm age